(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, the existence of viscous solutions of a hyperbolic equilibrium law system derived from the nonlinear entropy moment closure of a dynamic equation is established. In addition, by using the natural entropy of the system, some higher order estimates of some viscosity solutions are obtained.